2018
DOI: 10.1210/jc.2017-02378
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Antenatal Thyroid Screening II: Effect of Treating Maternal Suboptimal Thyroid Function on Child Cognition

Abstract: Maternal thyroxine during pregnancy did not improve child cognition at age 9.5 years. Our findings confirmed CATS-I and suggest that the lack of treatment effect may be a result of the similar proportion of IQ < 85 in children of women with normal-GTF and SGTF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 36 publications
3
64
1
7
Order By: Relevance
“…Many polluting chemical substances can interfere with thyroid hormone (TH) metabolism, which may lead to abnormalities in the neurological development of a foetus or child . However, maternal thyroxine supplement during pregnancy did not improve children's cognitive function …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many polluting chemical substances can interfere with thyroid hormone (TH) metabolism, which may lead to abnormalities in the neurological development of a foetus or child . However, maternal thyroxine supplement during pregnancy did not improve children's cognitive function …”
Section: Introductionmentioning
confidence: 92%
“…24 However, maternal thyroxine supplement during pregnancy did not improve children's cognitive function. 25 Pharmacotherapy is an effective treatment option for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…A previous survey among European Thyroid Association (ETA) members revealed that 42% of respondents screened all pregnant women and 43% adopted a case-finding approach; in another survey, 75% of Iranian endocrinologists opted for targeted screening, whilst universal screening was supported by 57% in Israel and by 43% in Latin America [9][10][11][12]. Two large-scale trials failed to demonstrate any benefit of LT4 on cognitive outcomes, and a recent study found a similar proportion of children with an IQ < 85 from women with normal and suboptimal gestational thyroid function [13][14][15]. Although the official stance of international endocrine societies was neither "for" nor "against" universal screening, it is clear that the majority of endocrinologists in the present survey supported universal screening, also due to overestimating of the benefits derived from treating SCH [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…However, given that recent findings have indicated that also high maternal TH concentrations are associated with lower offspring IQ, it is also possible that overtreatment may underlie the negative findings as 10% of treated women were in need of a dose reduction . Currently, important follow‐up studies of the CATS trial are being performed to identify any potential harms in women with high TH concentrations due to treatment with levothyroxine …”
Section: The Effects Of Treatmentmentioning
confidence: 99%
“…16,78 Currently, important follow-up studies of the CATS trial are being performed to identify any potential harms in women with high TH concentrations due to treatment with levothyroxine. 79,80 The TTMTDP trial was performed in the United States and screened close to 100.000 women, those with hypothyroxinemia or subclinical hypothyroidism (defined by the 2.5th and 97.5th percentile cut-offs) were randomized to receive a placebo or levothyroxine in a dosage considerably lower than the CATS trial, namely 50 or 100 μg, respectively. 81 81 Although this is in line F I G U R E 2 The power to detect a statistically significant effect of levothyroxine treatment on child IQ for available RCTs.…”
Section: The Effec Ts Of Tre Atmentmentioning
confidence: 99%